Notes on the play Acima de tudo: sociology and philosophy as bases for theatrical creation (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The article describes the methodology used to create the play Acima de tudo - anti-fascist theater, emphasizing the way in which dramaturgy and staging articulated the theoretical bases studied. Neofascism was approached from philosophical and sociological sources that made it possible to establish parallels between the period of Nazi Germany and Brazil today, the most evident being the mobilization, for totalitarian ideas, of the feeling of loneliness among the crowd. The cell phone was taken as a symbol of this massively hyperconnected loneliness that generated fascism in Brazil and used in the staging both as an object of the scene and as inspiration for the entire spectacle.
Keywords: Antifascist theater; Political theater; Dramaturgy; Theater and sociology; Theater and philosophy